Pengaruh PDRB, Pengangguran, dan Pendidikan Terhadap Kemiskinan Di Kabupaten Tanah Laut Tahun 2011-2021 - Pratiwi, Khovifah Septi; Sa'roni, Chairul (PPJP ULM, 2023)
This study was conducted to determine the GRDP (Gross Regional Domestic Product), unemployment, and education that affect poverty in Tanah Laut Districts and which factors have a major influence. This study used secondary data from 2011-2021 and multiple linear regression analysis tools, using test f, Test t, and test R- square (R2). As a result of this study, GRDP and unemployment significantly affected poverty in Tanah Laut Districts, while education didn’t significantly affect poverty in Tanah Laut Districts.